Memoir of a snail [videorecording (Blu-Ray)] - Elliot, Adam, 1972-; Kats-Chernin, Elena; Thompson, Gerald (Cinematographer) (IFC Films, 2025)
After a series of misfortunes, a snail-collecting, melancholic misfit learns how to find confidence within herself amid the clutter of everyday life.